Extraction of ZnO thin film parameters for modeling a ZnO/Si solar cell - Chala, Slimane; Sengouga, Nouredine; Yakuphanoğlu, Fahrettin; Rahmane, Saad; Bdirina, Madani; Karteri, Ibrahim (Pergamon-Elsevier Science Ltd, 2018)
Zinc oxide (ZnO) is a semiconductor with promising electrical and optical properties. Pure ZnO is an n-type degenerate semiconductor. It is almost entirely transparent in the optical region of the electromagnetic spectrum. In this work sol gel spin-coating method was used to grow a ZnO thin film from Zinc acetate decomposition. The optical properties of the thin film were extracted and investigated. A ZnO/p-Si heterostructure solar cell was realized using this film and its performance (efficiency) was found to be quite poor. A numerical procedure is used to elucidate this poor performance. A first step is to use the extracted optical parameters in the simulation. However, these parameters did not lead to the reproduction of measured current-voltage and figures of merit of the solar cell by simulation when other parameters of ZnO are taken from literature. It was therefore considered that ZnO is similar to an amorphous semiconductor with a continuous distribution of states in its band gap. The density of states model used is composed of tail bands and Gaussian distribution deep level bands. Eventually, and by adjusting the constituents of the band gap states and by increasing the surface recombination velocity in ZnO/p-Si interface, it was possible to obtain a good agreement between simulated and measured J-V characteristics of this solar cell. (C) 2018 Elsevier Ltd. All rights reserved.
10th International Conference on Sustainable Energy and Environmental Protection (SEEP) -- JUN 27-30, 2017 -- Univ W Scotland, Inst Engn & Energy Technologies, Bled, SLOVENIA
Keywords: Sol-gel; ZnO thin film; Solar cell; Simulation; Defects